Bone and Cartilage from Stem Cells: Growth Optimalization and Stabilization of Cell Phenotypes - Gordeladze, Jan O; Reseland, Janne E; Karlsen, Tommy A; Jakobsen, Rune B; Engebretsen, Lars; Lyngstadaas, Ståle P; Duroux-Richard, Isabelle; Jorgensen, Christian; Brinchmann, Jan E (IntechOpen, 2011)
None